MANAJEMEN KELAS ISLAMI KURIKULUM 2013 DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK KELAS VI SD DI ERA 4.0 - Yufi Latmini Lasari; Afina Annisa (STKIP Pesisir Selatan, 2020)
Islamic class management is important in shaping the character of students in the 4.0 era. But in reality, in this era of 4.0, it is often found that the character of students, especially those in Elementary Schools (SD), has started to diverge. Based on these facts, this research was conducted to describe the form of Islamic class management in the 2013 Curriculum in shaping the character of the VI-grade elementary school students in the era 4.0. The research method used is a descriptive qualitative method. In the research carried out it was found that 1) The character building of students in era 4.0 was carried out in three stages, namely planning, actuating and controlling, and 2) Integrating 18 values of character building and 5 values of strengthening character education. (PPK) into learning themes and sub-themes. Based on the results of the research, it was found that the character building of students in the 4.0 era could be done by implementing Islamic class management in learning activities.